INFLUENCING FACTORS ON COSTS AND DECISION MAKING . A LOOK AT THE BAKERY INDUSTRY - Florina LUP; Carmen SCORTE; Daniela ZAPODEANU (Annals of the University of Oradea: Economic Science)
The economic growth and development of any country is determined by the future of the economic entities in each sector, and this future is an important objective, with a decision-making process that will be influenced by various factors. But what are the factors influencing bread consumption, what are the factors influencing costs and decisions in this sector? The objectives of this paper are to answer some general and specific questions in this field: What are the factors influencing costs? How can costs influence the production decision and the consumption decision? Can the concept of circular economy influence costs? Do macro-economic issues influence costs and decisions? The paper is an empirical, quantitative research, based on the analysis of cost information, analysis of cost changes and the impact of factors that we consider to be determinants: the cost of purchasing raw materials under the influence of inflation, circular economy principles and other pedoclimatic or geopolitical factors, the cost of labour under the influence of legal regulations, the cost of energy under the influence of inflation, the energy crisis, geopolitical factors. In order to have a concrete perspective, we started from a case study of an entity that has an activity authorized under CAEN code 1071 Manufacture of bread; manufacture of cakes and fresh pastry goods. The analysis of cost information and the calculation of short-term decision indicators according to the CVP model started from the concrete situation in March 2023 to analysing the situation in March 2024 while taking into account the inflation confirmed by BNR and the legislative changes and trying a prospective analysis for March 2025.